Scientists and the Atomic Bomb, 1945 (pg. 4) (1945)
1945 1945-1960 "Scientists and the Atomic Bomb, 1945 (pg. 4)" [HFR0130d], 1945 The Association of Scientific Workers issued this statement on the dropping of atom bombs on Japan in November 1945. It expresses concern that atomic power should be developed for peaceful purposes and supports freedom of information to combat the increasing secrecy that was beginning to surround science research. The statement reproduces a letter that the Association's Vice-President, Professor J. D. Bernal, had sent to the Times newspaper.